Determinants of QRIS Payment Method Usage for Employees in Urban Areas - Christian, Michael; Indriyarti, Eko Retno (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2024)
By 2024, the quantity of Quick Response Code Indonesian Standard (QRIS) users in Indonesia is projected to reach 51 million. The usage of QRIS as a cashless payment system is gaining widespread acceptance. Nevertheless, research on cashless payment methods, including QRIS, indicates that usage behavior is significantly affected by multiple variables. Conversely, prior research has predominantly concentrated on consumers' age or generational backgrounds. This study seeks to examine the factors influencing QRIS usage behavior, specifically considering the backgrounds of employees in metropolitan regions, particularly Greater Jakarta. This research employs a quantitative methodology via a questionnaire survey to gather primary data. This study demonstrates, using SmartPLS, that mobile ease of use and perceived compatibility significantly influence QRIS usage behavior. Conversely, relative advantage and social influence indicate a different outcome. This is mostly attributable to the functions and attributes of QRIS, which is no longer an innovative product, having been preceded by several e-wallets. Further research could benefit from additional information on the background of e-wallet utilization, the incorporation of supplementary variables into the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model, and the expansion of studies to encompass other urban regions.